The Particularities of the Structural Components of the Students' Educational Process, for Improving Skills in the Instructive-Tourism Practice - E. Lungu; N. Nastas (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
The content of the practice in higher education institutions assumes the position of the worker in the field of tourism, who, in addition to office work, is put in the position to go on the route, and this fact can only be achieved through an instructive-tourism practice. The subject of the research focused on the instructive-tourism practice that can have various structural components must be implemented taking into account various aspects of the tourism industry. The methods that provided us with the expected results included the analysis of the specialized literature and the structural aspects of the tourist instructive practice process. All of this presupposes the implementation of some modules for practical field activities, necessary in the training of students' professional skills. Thus, the obtained results lead us to conclude that the diversification of student practices is essential in their professional training.